Communication is power - The Center for Humanities; Contemporary Arts Media (Australia : Contemporary Arts Media (distributor), 2005)
Advertising, violence, growing of electronic media in politics. Advertising, in one form or another, will appear in any society where there is trade or competition. Understanding the techniques of advertising can give insight into many other forms of mass persuasion. For the methods used to sell us products are also used to sell us candidates, ideas, even life styles
Title from container
DVD format
Keywords: Advertising; Business communication